P8 Follow up of sublingual immunotherapy in a paediatric population at cork university hospital. (June 2019) - O'Donnell, Sinead; Morris, Megan; Hourihane, Jonathan
Abstract : Introduction: Allergic rhinitis is an immune-mediated response of the nasal mucosa to allergens, which is clinically characterised by paroxysms of sneezing, rhinnorhea, and nasal obstruction which is often accompanied by itching of the eyes, nose and palate. In the most severe cases, patients can still have a reduced quality of life despite optimal treatment with antihistamines, eye drops and nasal sprays. When the symptoms of allergic rhinitis persist, they can have a dramatic impact on the quality of life of the child and their family. Untreated symptoms can have a detrimental effect the child's sleeping pattern which consequently can impact negatively on their growth potential, cognition and participation in social activities. Sublingual Immunotherapy (SLIT) can alter a patient's sensitivity to inhaled allergens and improve symptoms which do not respond to the standard therapies. Aim and methods: The aims of this study were to assess the effect SLIT had on patients both during the treatment and after. Effects were determined by retrospective chart review. 38 children (age 5–17) completed 3 years of SLIT at Cork University Hospital between 2010 and 2016. 34 patient/guardians were contacted by telephone to provide additional information; the remaining 4 were unreachable by phone. Results: In the study population, Immunotherapy was prescribed for house dust mites (24%) and grass pollen (76%). Treatment with SLIT reduced symptoms of allergic rhinitis in 91% of patients during SLIT. 62% had an improvement in symptoms post completion of therapy and 29.4% maintained the level of reduction during treatment. There was a reported drop in the amount of patients using medications such as antihistamines, nasal sprays and eye drops. 50% of the patients had a diagnosis of asthma as well as allergic rhinitis. 76% of these patients had an improvement of their asthma symptoms, resulting in a reduction of inhaler use. Overall, 88% of the patients were satisfied with the SLIT and they would recommend it to others. Discussion: The effect of grass pollen and HDM allergen SLIT for allergic rhinitis is substantial and sustained in medium term, patients experienced a reduction in both symptoms and medication use. There is also an effect of SLIT on asthma which must be noted, as these patients also experienced a reduction in symptoms and medication use.